2003
DOI: 10.1242/jcs.00261
|View full text |Cite
|
Sign up to set email alerts
|

hRUL138, a novel human RNA-binding RING-H2 ubiquitin-protein ligase

Abstract: Cellular as well as viral RNAs are usually found complexed with proteins. In an attempt to identify proteins that interact with transcripts of hepatitis B virus (HBV), a DNA virus that replicates through reverse transcription, a partial cDNA was isolated from a human cDNA expression library whose gene product bound to an HBV-derived RNA. Using an overlapping clone from a molecular hybridization screen a full-length cDNA was assembled. It contained a large open reading frame for a 1208 amino-acid protein of 138… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…S1b). The latter group revealed that two E3 ubiquitin ligases with RNA-binding domains, Mex3b (a RING- and KH domain-containing E3 ubiquitin ligase 16 ) and Dzip3 (a RING- and KKKTK domain-containing E3 ubiquitin ligase 17 ) selectively interacted with HOTAIR (Supplementary Fig. S1b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1b). The latter group revealed that two E3 ubiquitin ligases with RNA-binding domains, Mex3b (a RING- and KH domain-containing E3 ubiquitin ligase 16 ) and Dzip3 (a RING- and KKKTK domain-containing E3 ubiquitin ligase 17 ) selectively interacted with HOTAIR (Supplementary Fig. S1b).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 6a, a mutant Dzip3 (bearing a point mutation in the RING domain, essential for ubiquitination) expressed in HeLa cells from plasmid pTRUF-hRUL138(C1187S) was unable to ubiquitinate Ataxin-1 (top) or promote its degradation (bottom), as compared with the effect of expressing the wild-type counterpart pTRUF-hRUL138(WT) 17 . In addition, ectopic expression of a mutant Ataxin-1(82Q) that cannot bind RNA 21 indeed did not interact with HOTAIR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Direct screens identified a 65 kDa nuclear protein [84] of unknown sequence and, more recently, a novel large RNA-binding ubiquitin ligase, hRUL138 [85] , as potential cellular ε RNA interaction partners. However, their roles in the viral life-cycle are not known.…”
Section: Structure Of the Rna Encapsidation Signal εmentioning
confidence: 99%
“…The hRUL138 (human RNA-binding ubiquitin ligase 138) protein was initially discovered in a screen for human proteins which bind RNA HBV-ε-derived probes [31]. This protein encodes a RING-H2 type domain and, in vitro, can autoubiquitinate, as well as transubiquitinate targets.…”
Section: Ring+kkktk Domain-containing Proteins: Hrul138/2a-hubmentioning
confidence: 99%
“…This protein encodes a RING-H2 type domain and, in vitro, can autoubiquitinate, as well as transubiquitinate targets. In the absence of a known RRM within the hRUL138 sequence, Kreft and Nassal [31] used deletion mapping and Northwestern blotting to identify a novel KKKTK (Krich) region required for RNA binding. Furthermore, GFP (green fluorescent protein)-tagged hRUL138 is expressed in cytosolic punctate structures probably resembling stress granules.…”
Section: Ring+kkktk Domain-containing Proteins: Hrul138/2a-hubmentioning
confidence: 99%